Beyond the systems versus package debate - Merchant, Kenneth A.; Otley, David (Accounting, Organizations and Society, 2020)
This discussion paper outlines the wider context from which the systems versus package debate has emerged, and draws on the papers included in this Special Issue to make suggestions for future progress. It argues that much research work has focused on narrow aspects of management control systems and has often detached these from their wider organizational contexts, diminishing its value. Researchers should recognize that management control systems are complex in themselves, and they interact in complex ways with the settings in which they are used. We describe various consequences of this situation and provide suggestions as to how research can be improved. We conclude that there is a need for more field-based studies by academics who are better connected with the world of practice. Only in this way will our research work both lead to better, more reliable, theories of MCS design and use and also be useful to practitioners.